Adsorption Characteristics of Coal-based Activated Carbons. II. Adsorption of Water Vapour, Pyridine and Benzene - Th. El-Nabarawy; N.Sh. Petro; S. Abdel-Aziz (Adsorption Science & Technology)
Chemically-activated carbons were prepared by carbonizing Maghara coal with different amounts of phosphoric acid at 873 K. Steam-activated carbons of different burn-off were prepared by gasifying non-activated carbon prepared by carbonization at 873 K with steam at 1173 K. Samples of steam-activated carbons were also treated with concentrated nitric acid or with potassium dichromate. The adsorption of water vapour and benzene was determined at 308 K. The adsorption of pyridine was followed on the chemically-activated carbons at 343 K. The adsorption of water vapour was found to be related to the surface area and the amount of carbon–oxygen groups. Some of the adsorbed water was found to be specifically held to the surface and could be used to determine the number of carbon–oxygen groups on the surface. Two mechanisms are involved in the adsorption of pyridine on the carbons investigated. These are physisorption on the oxygen-free surface and chemisorption on carbon–oxygen groups of an acidic nature. Benzene may be vertically oriented in micropores, horizontally oriented in wider pores and may be even inaccessible to the fraction of the surface located in ultramicropores. Benzene adsorption is also retarded by the existence of a high concentration of carbon–oxygen groups oh the surface.